Toxicity of barbatimão to Apis mellifera and Scaptotrigona postica, under laboratory conditions - Cintra, Priscila [UNESP]; Malaspina, Osmar [UNESP]; Bueno, Odair Correa [UNESP] (Taylor & Francis, 2003)
Two species of plants commonly known as barbatimão occur in Brazil, Stryphnodendron adstringens (Fabaceae) (true barbatimão) and Dimorphandra mollis (Caesalpiniaceae) (false barbatimão). These two species have a similar flowering period and are considered by beekeepers to cause bee mortality during this period. Flowers were collected from both species, dehydrated, ground and incorporated into an experimental diet for bees of two different species, Apis mellifera and Scaptotrigona postica. Both plant species were toxic to A. mellifera, reducing their median survival. D. mollis was toxic to S. postica, and Stryphnodendron adstringens reduced median survival of this bee species even when used at a concentration of 2.5%. In a choice experiment carried out with A. mellifera and the two plant species, the honey bees could choose not to feed on the diets containing the flowers, and feed on sugar and honey instead, but they did not. This shows us that the flowers of S. adstringens were not repellent to the bees. The plants were more toxic to A. mellifera than to Scaptotrigona postica, a result that can be explained by the fact that A. mellifera was introduced into Brazil whereas S. postica is a native stingless bee. © 2003 International Bee Research Association.
Keywords: Apis mellifera; Barbatimão; Brazil; Dimorphandra mollis; Honey bees; Scaptotrigona postica; Stingless bees; Stryphnodendron adstringens; Toxicity